TAMI-17. RELATIONSHIP BETWEEN IRON METABOLISM, IMMUNE CELL INFILTRATION AND SEX-BASED SURVIVAL DIFFERENCES IN GLIOMAS. (9th November 2020) - Nesterova, Darya; Lee, Sang; Zacharia, Brad; Proctor, Elizabeth; Lathia, Justin; Rubin, Joshua; Berens, Michael; Barnholtz-Sloan, Jill S; Connor, James
Abstract: Iron plays a central role in cellular metabolism, both in normal cellular functioning and in tumorigenesis. Recent evidence has shown sex-based survival differences in glioblastoma (GBM) may be related to differential expression of metabolism genes. We previously reported the iron regulating gene, HFE, was shown to have a sex-based survival impact in both low-grade gliomas and GBM. We additionally found that females with low HFE expressing tumors have significantly higher survival than males in GBM. To evaluate the relationship between iron gene expression and sex-based survival differences in GBM, we analyzed TCGA GBM gene expression and clinical data. We first analyzed the impact of iron genes on sex-based survival. In addition to HFE, FTL, TFRC, TF, and SLC39A8 (ZIP8), also showed sex-based survival differences. We then compared correlations of HFE and other iron genes to identify whether male and female GBMs differ in iron regulation and metabolism. HFE expression is significantly positively correlated with HMOX1, SLC25A28, SLC11A2, FTH1, HAMP, and TFR2 only in females. Alternatively, HFE expression is negatively correlated with ACO2 (mitochondrial aconitase) in males and ACO1 (cytoplasmic aconitase) in females. We noted that the expression of certain iron genes was highly associated with immune cell infiltration based on sex . TFR2, LRP1, and XIST expression were negatively correlated with low immune cell infiltration in females, but not males. Alternatively, in males, SLC11A2, ACO2, FOXO1, HIF1a, and HAMP genes were negatively correlated with immune infiltration. This suggests that differences in iron regulation between males and females may be contributing to differences in immune function and subsequent survival in GBM. These data suggest that the iron signature of a tumor reflects and possibly drives the metabolic and immune landscape of the tumor microenvironment thereby directly impacting survival differences between male and female GBMs.